Utilization of CapCut and Canva as Learning Media to Enhance Visual Learning Effectiveness in Environmental Education at SMP Kanisius Sumber - Ekowati , Maria Atik Sunarti; Poernomo, Moyo Hady; Silvano, Gabriel; Saputra, Unggul Widya (CV. Science Tech Group, 2024)
This article discusses the use of CapCut and Canva applications as learning media to improve the effectiveness of visual learning at SMP Kanisius Sumber. In the digital era, the use of technology in learning is increasingly becoming a necessity, especially in creating interesting and easy-to-understand teaching materials for students. CapCut, a video editing application, and Canva, a graphic design platform, are tools that enable teachers and students to produce creative and innovative learning materials. This study aims to explore the potential of both applications in improving the understanding of learning concepts through visual media. The results of the study indicate that the integration of CapCut and Canva in the learning process can help students understand the material more easily, increase their engagement, and enrich the learning experience with more interactive and interesting content. This article also provides recommendations for further implementation in the context of education in junior high schools, especially in maximizing the use of technology-based learning media.